2023
DOI: 10.1186/s12890-023-02547-9
|View full text |Cite
|
Sign up to set email alerts
|

Circulating choline levels are associated with prognoses in patients with pulmonary hypertension: a cohort study

Yicheng Yang,
Beilan Yang,
Bingyang Liu
et al.

Abstract: Backgrounds Mounting evidences have highlighted the association between metabolites and cardiovascular diseases. Our previous works have demonstrated that circulating metabolite, trimethylamine oxide, was associated with prognosis of patients with pulmonary hypertension (PH). Choline is a precursor of trimethylamine oxide and its role in PH remains unknown. Here, we aimed to validate the hypothesis that circulating choline levels were associated with prognoses in patients with PH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Previous studies have demonstrated its potential biomarker role in CVDs, including acute coronary syndrome [ 133 , 134 ] and hypertension [ 135 ]. Our team is the first to investigate the association between circulating choline levels and PH patients' prognosis, and we found similar biomarker effects of the metabolite in PH field [ 136 ]. Additionally, our team has discovered and defined TMAVA as another TMAO‐associated metabolite [ 39 ].…”
Section: Gut Microbiota‐dependent Metabolites In Phmentioning
confidence: 86%
“…Previous studies have demonstrated its potential biomarker role in CVDs, including acute coronary syndrome [ 133 , 134 ] and hypertension [ 135 ]. Our team is the first to investigate the association between circulating choline levels and PH patients' prognosis, and we found similar biomarker effects of the metabolite in PH field [ 136 ]. Additionally, our team has discovered and defined TMAVA as another TMAO‐associated metabolite [ 39 ].…”
Section: Gut Microbiota‐dependent Metabolites In Phmentioning
confidence: 86%
“…For instance, choline, a precursor of microbiota-derived metabolites that promote vascular ageing, whose role was already demonstrated in hypertension, atherosclerosis, myocardial infarction [80], and heart failure [81,82], was investigated as a biomarker of PH of various etiologies. Specifically, high baseline choline levels (representative of a western diet [83]) were significantly associated with adverse outcomes in PAH patients, as well as with elevated NT-proBNP levels, higher WHO-FC, and a low cardiac output index [84]. However, they are far from being used in clinical practice, and no data are available with regard to the correlation between the levels of these markers and disease progression during specific PAH therapy.…”
Section: Role Of Biomarkers In the Prognosis Of Pahmentioning
confidence: 99%